2019
DOI: 10.20471/acc.2019.58.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Duration as a Predictor of Childhood Lifestyle Habits, Overweight and Obesity in Second- And Third-Grade Schoolchildren in Croatia

Abstract: -Breastfeeding is related to better overall health in adult life and is one of the commonly described protective factors for childhood obesity. The purpose of this study was to describe the relationship between breastfeeding duration, childhood lifestyle habits, overweight and obesity in a cohort of Croatian second-and third-grade schoolchildren. randomly selected second-and thirdgrade children aged 6-11 years (n=5662) were measured for weight and height in order to calculate nutritional status for each child.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Breastfeeding duration is an important confounder of child feeding and growth (Martin, 2001;Haider & Saha, 2016;Lang Morović & Musić Milanović, 2019). Thus, we also re-run the analyses for only children with breastfeeding duration.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Breastfeeding duration is an important confounder of child feeding and growth (Martin, 2001;Haider & Saha, 2016;Lang Morović & Musić Milanović, 2019). Thus, we also re-run the analyses for only children with breastfeeding duration.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Australian researchers conducted a survey with 2868 infants and found that children who breastfed for less than 4 months had a significantly increased risk of childhood weight exceeding the 95 th percentile of children of the same age and sex [ 41 ]. Research in Croatia indicated that breastfeeding for more than 6 months was a protective factor for overweight and obesity in children aged 6 to 11 years [ 42 ]. However, our study considered that infants who were breastfed for more than 12 months were significantly less likely to be overweight and obese in their childhood and adolescent years.…”
Section: Discussionmentioning
confidence: 99%
“…Morovic et al 15 Criança que amamentaram por menos de 6 meses têm maior chance de desenvolver sobrepeso e obesidade.…”
Section: 566unclassified